From liberal to restrictiveness: an overview of 25 years of retail planning in England - Guimarães, Pedro (2018)
The development of cities to peripheral locations had a profound impact on town centres. Alongside with these changes, retail also evolved, whether locating peripherally, whether through the appearance of new formats. The public intervention through retail planning has been focusing on the protection of town centres and in the preservation of small retail. In this paper we have analysed retail planning undertaken in England in the last 25 years. We conclude that two different models of retail planning were developed and its effectiveness wasn’t achieved because it was never completely restrictive due to the balance between economic and non-economic factors.